Interpregnancy Interval and Subsequent Severe Maternal Morbidity: A 16-Year Population-Based Study From California. Issue 6 (5th February 2021) - Liu, Can; Snowden, Jonathan M; Lyell, Deirdre J; Wall-Wieler, Elizabeth; Abrams, Barbara; Kan, Peiyi; Stephansson, Olof; Lyndon, Audrey; Carmichael, Suzan L
Abstract: Interpregnancy interval (IPI) is associated with adverse perinatal outcomes, but its contribution to severe maternal morbidity (SMM) remains unclear. We examined the association between IPI and SMM, using data linked across sequential pregnancies to women in California during 1997–2012. Adjusting for confounders measured in the index pregnancy (i.e., the first in a pair of consecutive pregnancies), we estimated adjusted risk ratios for SMM related to the subsequent pregnancy. We further conducted within-mother comparisons and analyses stratified by parity and maternal age at the index pregnancy. Compared with an IPI of 18–23 months, an IPI of <6 months had the same risk for SMM in between-mother comparisons (adjusted risk ratio (aRR) = 0.96, 95% confidence interval (CI): 0.91, 1.02) but lower risk in within-mother comparisons (aRR = 0.76, 95% CI: 0.67, 0.86). IPIs of 24–59 months and ≥60 months were associated with increased risk of SMM in both between-mother (aRR = 1.18 (95% CI: 1.13, 1.23) and aRR = 1.76 (95% CI: 1.68, 1.85), respectively) and within-mother (aRR = 1.22 (95% CI: 1.11, 1.34) and aRR = 1.88 (95% CI: 1.66, 2.13), respectively) comparisons. The association between IPI and SMM did not vary substantially by maternal age or parity. In this study, longer IPI was associated with increased risk of SMM, which may be partly attributed to interpregnancy health.